2000
DOI: 10.1152/jn.2000.83.5.3188
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Wrist in Three-Joint Arm Movements to Multiple Directions in the Horizontal Plane

Abstract: In a reaching movement, the wrist joint is subject to inertial effects from proximal joint motion. However, precise control of the wrist is important for reaching accuracy. Studies of three-joint arm movements report that the wrist joint moves little during point-to-point reaches, but muscle activities and kinetics have not yet been described across a range of movement directions. We hypothesized that to minimize wrist motion, muscle torques at the wrist must perfectly counteract inertial effects arising from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 39 publications
(61 reference statements)
2
21
0
1
Order By: Relevance
“…For instance, in a step tracking task during which a constant wrist flexion was combined with progressively larger elbow extensions, muscle-activation patterns at the wrist were modified in relation to the increasing interaction torque acting at the wrist as a result of elbow motion (Cooke and Virji-Babul 1995). Similar results were obtained in studies of single-and multijoint pointing movements involving shoulder and elbow motion alone (Almeida et al 1995;Gribble and Ostry 1999;Sainburg et al 1995) or combined with wrist motion (Koshland et al 2000). Moreover, the modulations of EMG activity at stationary joints contingent on the magnitude of the interaction torque were shown to occur prior to the onset of motion at adjacent joints, suggesting that they arose through feedforward rather than feedback control (Gribble and Ostry 1999).…”
Section: Anticipatory Motor Compensation For Self-generated Interactisupporting
confidence: 57%
See 1 more Smart Citation
“…For instance, in a step tracking task during which a constant wrist flexion was combined with progressively larger elbow extensions, muscle-activation patterns at the wrist were modified in relation to the increasing interaction torque acting at the wrist as a result of elbow motion (Cooke and Virji-Babul 1995). Similar results were obtained in studies of single-and multijoint pointing movements involving shoulder and elbow motion alone (Almeida et al 1995;Gribble and Ostry 1999;Sainburg et al 1995) or combined with wrist motion (Koshland et al 2000). Moreover, the modulations of EMG activity at stationary joints contingent on the magnitude of the interaction torque were shown to occur prior to the onset of motion at adjacent joints, suggesting that they arose through feedforward rather than feedback control (Gribble and Ostry 1999).…”
Section: Anticipatory Motor Compensation For Self-generated Interactisupporting
confidence: 57%
“…Studies addressing the issue of compensation for self-generated interaction torques have shown that the phasic electromyographic (EMG) activity in muscles spanning joints with constant kinematics is influenced by the characteristics of motion in adjacent joints (Almeida et al 1995;Cooke and Virji-Babul 1995;Gribble and Ostry 1999;Koshland et al 2000;Sainburg et al 1995). For instance, in a step tracking task during which a constant wrist flexion was combined with progressively larger elbow extensions, muscle-activation patterns at the wrist were modified in relation to the increasing interaction torque acting at the wrist as a result of elbow motion (Cooke and Virji-Babul 1995).…”
Section: Anticipatory Motor Compensation For Self-generated Interactimentioning
confidence: 99%
“…Given the growing body of evidence that the motor system is capable of forming feedforward, "internal models" of mechanical and dynamical contexts including joint interaction torques (Gribble and Ostry 1999;Koshland et al 2000;Sainburg et al 1995Sainburg et al , 1999, one may raise the question of why the CNS used cocontraction and not changes in reciprocal muscle activation to achieve greater movement accuracy. It has been proposed that cocontraction may be a strategy that is used by the CNS early in learning a novel motor task to achieve greater accuracy in the absence of a fully formed "internal model" of dynamics-and that with ongoing practice, cocontraction may be reduced as learning takes place and internal representations are built up to achieve greater accuracy using changes in reciprocal, feedforward motor commands (Osu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Here we test the hypothesis that the CNS modulates cocontraction for arm movements in the context of different accuracy constraints. Increases in joint stiffness brought about by muscle cocontraction would have a beneficial effect on limb stability and hence movement accuracy by reducing the perturbing effects of joint interaction torques (Gribble and Ostry 1999;Koshland et al 2000) and external forces (Gomi and Haggard 2001;Lacquaniti and Maioli 1989;Osu et al 2002;Thoroughman and Shadmehr 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The triphasic EMG has been extensively studied. It arises during single-and multijoint movements and is seen both in muscles acting across moving joints and acting across stationary joints that must be stabilized during movement of other parts of the limb (Brown and Cooke 1990;Cooke and Brown 1990;Corcos et al 1989;Flanders 1991;Ostry 1998, 1999;Hoffman and Strick 1999;Koshland et al 2000;Wadman et al 1980). It can even arise during very rapid (Ïœ120 ms) targeted isometric-force pulses, possibly to compensate for the low-pass filter properties of the musculoskeletal plant (Ghez and Gordon 1987).…”
Section: Task Dynamics and Muscle Activitymentioning
confidence: 99%